Metal–Organic Frameworks Constructed from Iron‐Series Elements for Supercapacitors. Issue 5 (19th October 2021) - Wang, Kuaibing; Guo, Yuxuan; Zhang, Qichun
Abstract : Iron‐series (Fe, Co, and Ni) containing metal–organic frameworks (MOFs) have gained great concern in supercapacitors (SCs) because of their tailorable architectures, multiple redox‐active sites, and intriguing properties. Given the importance of porosities in MOFs for charge transmission, an essential assessment of their designs, preparation methods, and engineering technologies is strongly required to further explore and optimize SCs. Through empowering conductive backbones and redox‐active centers, iron‐series containing MOF‐based electrodes have made outstanding achievements recently. This review aims to summarize these core reports on iron‐series containing MOFs. Correspondingly, the design strategy, the reason for compositing, the strategy of introducing heteroatoms, and the current divergences on structural alteration mechanisms are discussed. Potential bottleneck issues and coping strategies are also perspectively discussed to guide future optimization. Abstract : Recent progress on iron‐series metal–organic framework (MOF)‐based materials (including pristine or composite Fe‐, Co‐, and Ni‐based MOFs) for supercapacitors around the design strategy, the specific performances of capacities and energy/power densities, the reason for compositing various conductive matrixes, the strategy of introducing heteroatoms into the lattice, and the current divergences on structural alteration mechanisms are summarized and outlooked.